Judeans in Babylonia : a study of deportees in the sixth and fifth centuries BCE - Alstola, Tero (Culture and history of the ancient Near East,, 2020)
"In Judeans in Babylonia, Tero Alstola presents a comprehensive investigation of deportees in the sixth and fifth centuries BCE. By using cuneiform documents as his sources, he offers the first book-length social historical study of the Babylonian Exile, commonly regarded as a pivotal period in the development of Judaism. The results are considered in the light of the wider Babylonian society and contrasted against a comparison group of Neirabian deportees. Studying texts from the cities and countryside and tracking developments over time, Alstola shows that there was notable diversity in the Judeans' socio-economic status and integration into Babylonian society"--